Cultural Expression and Liturgical Theology in the Worship Songs Sung by British-Born Chinese - Tang, James Yat Man (Religions, 2024)
Multilingual and multicultural worship can take on many models and expressions. Initially, Chinese immigration to the UK in the 1950s and 1960s led to an increased population of churches. Many Chinese church services were conducted in Cantonese, catering to the needs of first-generation immigrants, mainly from Hong Kong. Yet, the children of these older generations grew up with a bicultural hybridized identity expressed first in small English-speaking youth groups that led to English-speaking worship services within Chinese churches. Contributing to the field of worship studies through music repertoire studies over four weeks in June and July 2017 at Birmingham Chinese Evangelical Church, we raised the following questions: (1) what do the chosen worship songs represent with regards to the liturgical theology and cultural expressions of this community and (2) how is self-perception and perception of the divine expressed in the lyrical themes of these songs? Our study revealed that singing English songs from the West dominated the corporate liturgical identity of these services. Yet, through a British-born Chinese evangelical cultural reading, some lyrical themes were particularly resonant within Chinese culture, such as honor, shame, reverence, and bowing.